Determinants of Corporate Social Responsibility in Nepalese Commercial Banks - Bastola, Sweekriti (Nepalese Journal of Management, 2024)
The study attempts to examine the determinants of corporate social responsibility in Nepalese commercial banks. Corporate social responsibilities (CSR) is the dependent variable and the selected independent variables are return on assets (ROA), return on equity (ROE), bank age (BA), bank size (BS) and liquidity. The study is based on primary as well as secondary data. The primary data consists of questionnaires to 125 respondents from 18 commercial banks. The secondary data includes the observations from 18 commercial banks for the period of 2014/15 to 2020/21. The secondary data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and the annual report of respective banks. The correlation coefficients and regression models are estimated to test the significance and importance of ROA, ROE, BA, BS and liquidity on determining CSR activities in Nepalese commercial banks.The result showed that ROA has a positive impact on CSR of Nepalese commercial banks. It indicates that increase in ROA of bank would leads to increase in CSR activites. Likewise, the results also showed that ROE has a positive impact on CSR. It means that higher the ROE, higher would be the CSR related activities. Similarly, the study also found that bank size is positively related to the bank CSR. This indicates that the larger the bank size, greater would be the CSR of such banks. Moreover, bank age also has a positive impact on CSR. It suggests that older banks are likely to perform greater CSR activities than newer banks. In addition, the study showed that liquidity has a negative impact on CSR. This means that higher the level of liquidity in the banks, lower would be the CSR activities of Nepalese commercial banks. The study revealed that the most dominant factor that determines the CSR is liquidity followed by ROE in the context of Nepalese commercial banks.